Inflammation and breast cancer. Metalloproteinases as common effectors of inflammation and extracellular matrix breakdown in breast cancer - Hojilla, Carlo V (BioMed Central, 2008)
Two rapidly evolving fields are converging to impact breast cancer: one has identified novel substrates of metalloproteinases that alter immune cell function, and the other has revealed a role for inflammation in human cancers. Evidence now shows that the mechanisms underlying these two fields interact in the context of breast cancer, providing new opportunities to understand this disease and uncover novel therapeutic strategies. The metalloproteinase class of enzymes is well studied in mammary gland development and physiology, but mostly in the context of extracellular matrix modification. Aberrant metalloproteinase expression has also been implicated in breast cancer progression, where these genes act as tumor modifiers. Here, we review how the metalloproteinase axis impacts mammary physiology and tumorigenesis and is associated with inflammatory cell influx in human breast cancer, and evaluate its potential as a regulator of inflammation in the mammary gland.